2014
DOI: 10.2147/opth.s66372
|View full text |Cite
|
Sign up to set email alerts
|

Customized epithelial debridement for thin ectatic corneas undergoing corneal cross-linking: epithelial island cross-linking technique

Abstract: Thin corneas with a minimum corneal thickness less than 400 μm after epithelial removal represent a contraindication to standard epithelium-off cross-linking (CXL) treatment due to a significant endothelial cell density decrease and potentiality of permanent haze development. Preoperative swelling of the cornea with hypoosmolar riboflavin solutions broadens the spectrum of CXL indications to thin corneas. However the iatrogenic swelling effect might not be durable throughout the CXL procedure increasing the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 15 publications
0
20
1
Order By: Relevance
“…Though thin cornea could be swelling to safe thickness (over 400 μ m) with hypoosmolar riboflavin solution, the iatrogenic swelling effect was short acting, and the thinnest CT decreased significantly at the end of hypoosmolar riboflavin application [ 53 ], thus increasing the risk of corneal scarring and endothelial cells' damage. To solve this problem, a new technique that is epithelial island cross-linking (EI-CXL) with customized pachymetry-guided epithelial debridement was introduced [ 54 ]. In Mazzotta Cosimo and Ramovecchi study [ 54 ], EI-CXL technique was performed on 10 keratoconus patients with thin cornea (range 368–391 μ m).…”
Section: Procedures and Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Though thin cornea could be swelling to safe thickness (over 400 μ m) with hypoosmolar riboflavin solution, the iatrogenic swelling effect was short acting, and the thinnest CT decreased significantly at the end of hypoosmolar riboflavin application [ 53 ], thus increasing the risk of corneal scarring and endothelial cells' damage. To solve this problem, a new technique that is epithelial island cross-linking (EI-CXL) with customized pachymetry-guided epithelial debridement was introduced [ 54 ]. In Mazzotta Cosimo and Ramovecchi study [ 54 ], EI-CXL technique was performed on 10 keratoconus patients with thin cornea (range 368–391 μ m).…”
Section: Procedures and Modificationmentioning
confidence: 99%
“…To solve this problem, a new technique that is epithelial island cross-linking (EI-CXL) with customized pachymetry-guided epithelial debridement was introduced [ 54 ]. In Mazzotta Cosimo and Ramovecchi study [ 54 ], EI-CXL technique was performed on 10 keratoconus patients with thin cornea (range 368–391 μ m). The epithelium in the paracentral and midperipheral cornea where the cornea is thicker was removed carefully and the thin apical cornea epithelium was preserved.…”
Section: Procedures and Modificationmentioning
confidence: 99%
“…Mazzotta and Ramovecchi 2014 presented a new surgical option for treating thin corneas known as epithelial island cross-linking technique. Partial epithelial islands on corneal thinnest point area left together with intrastromal riboflavin shield make a safe barrier for corneal endothelium protection [ 27 ]. Hafezi 2011 reported a failure of collagen cross-linking with hypoosmolar riboflavin solution in an extremely thin cornea and concluded that the increase in biomechanical resistance was not sufficient to stop the progression of the disease; therefore, minimal preoperative stromal thickness of 330 μ m needs to be a limit for a successful CXL procedure [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Four weeks after the treatment, stromal haze and demarcation line were detected in the corneal areas with epithelial debridement, but not in the areas with intact epithelium; deepithelialized stroma outside the cone region displayed total keratocyte apoptosis and honeycomb-like edema, whereas it was minimal beneath the intact epithelium [ 69 ]. In contrast, Mazzotta et al [ 70 ] demonstrated keratocyte apoptosis at an average depth of 160 μm under the epithelial island compared to 250 μm under the de-epithelialized area in 10 eyes with 1-year follow-up.…”
Section: Reviewmentioning
confidence: 94%